SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA MISKIN DENGAN METODE AHP DAN MOORA - Prasetyanti Devi Madyaratri; Indra Dharma Wijaya; Retno Damayanti (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
One of the efforts to realize national development priorities is through education. However, in reality there are still many Indonesian citizens who do not get the right to enroll in education because of their financial inadequacy. UU No. 20 Tahun 2003 established an assistance program called the Bantuan Siswa Miskin (BSM) or Cash Transfer Program for Poor Students. There are still many mistakes in determining BSM fund recipients because the selection is still done manually. Providing funding for eligible students cannot be done since the manual system makes it impossible to provide ones for the eligibles. The selection is also not based on the government criteria and is only determined by officers / teachers appointed by primary schools in Kab. Tulungagung. Therefore, a support system is needed to determine the right and accurate BSM scholarship recipients according to the criteria set by the government. MOORA and AHP methods were used because they can produce objective data. This Decision Making System has a data notification feature with email and ranking data. Based on the results of the questionnaire, the results of the assessment BSM Recipient Decision Support System assistance shows a good percentage of 47%, a good enough percentage of 39%, a quite difficult percentage 9.34% and currently quite difficult 4%. It can be concluded that this information system can help determine the BSM scholarship grant process optimally and right on the eligible targets